Horror a very short introduction - Jones, Darryl 1967- (Oxford University Press, 2021)
Fear is one of the most primal emotions, and one of the hardest to reason with and dispel. So why do we scare ourselves? Delving into the darkest corners of horror literature, films, and plays, Darryl Jones explores its monsters and its psychological chills, discussing why horror stories disturb us, and how they reflect society's taboos
Also issued in print: 2021. - Includes bibliographical references and index
Keywords: Geschichte; Horror; Terror; Supernatural; Horrorerzählung; Horrorfilm; Horrorliteratur; Kultur